The Effect Of Marketing Mix On Customer's Decision To Save On PT. Bank Muamalat Kendari Branch - Mahfudz; Tiara Juliana Jaya; Nur Laili Fikriah (Sekolah Tinggi Agama Islam At-Tahdzib, Ngoro, Jombang, Indonesia, 2020)
This research aims to find out how the marketing mix affects customers' decision to save on PT. Bank Muamalat Kendari Branch. This research uses quantitative methods using observation techniques, questionnaires and documentation. The sample used in this study was 89 customers who had saved up at PT. Bank Muamalat Kendari Branch. Based on the results of the research that has done it can say that marketing mix has a significant relationship because it can explain that the significant value of 0,000, the significant level is smaller than 0.05 or the value of t-count is higher than the value of t-table which means that PT. Bank Muamalat Kendari Branch can meet the needs and desires of customers so that customers feel satisfied in terms of products, the price of administration provided, promotion as well as excellent service and security, and strategic bank location. Therefore, the better service provided by the bank will have an impact on the increasing decision of customers to save on PT. Bank Muamalat Kendari Branch.